Cyclic Fatigue and Fracture Resistance in Contemporary Rotary File Systems: An Evidence-Based Review - Harsha Haridas; Chris Susan Abraham; Swapnil Ashok Mishra; Bhavani roopan vijayakumar; Akshaya Shinde; J.V. Karunakaran (The Bioscan, 2024)
Nickel-titanium (NiTi) rotary endodontic instruments have revolutionized root canal treatment. However, their clinical performance can be influenced by various factors, including material properties, design modifications, and sterilization techniques. The review explores the impact of material science innovations, such as the development of R-phase NiTi alloys and gold-wire NiTi instruments, on improving flexibility, fatigue resistance, and torsional resistance. Additionally, the significance of design modifications, including triangular cross-sections, variable tapers, S-shaped cross-sections, and modified tip designs, is discussed.The clinical implications of these advancements are highlighted, with a particular focus on cyclic fatigue resistance in curved canals Cyclic fatigue and fracture resistance are critical factors influencing the clinical success of rotary file systems in endodontics. Recent advancements, including heat-treated NiTi alloys, innovative designs, and surface modifications, have significantly improved these properties. This review provides an evidence-based analysis of these advancements and their implications for clinical practice.